2009
DOI: 10.1097/psy.0b013e3181a20c9c
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Increased Visceral Fat in Middle-Aged Women

Abstract: Objective-Mechanisms underlying the association between depression and increased cardiovascular risk remain poorly understood. Central adiposity is one potential pathway. Prior research has shown an association between depression and central adiposity but few studies have examined whether depressive symptoms are differentially associated with visceral adipose tissue (VAT), which is more metabolically active and confers greater cardiovascular risk than subcutaneous fat (SAT).Methods-We investigated the cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 58 publications
10
78
3
4
Order By: Relevance
“…Waist circumferenceconfirming the accumulation of visceral fatin female patientswith depression(> 90cm) has also been reported by otherauthors [5,25]. In the present study, the averagefat content was lowerin female and male urban residents (30% and29%, respectively) compared to female and male village inhabitants (37% and 30%, respectively), although statistically significant difference was found onlybetween women.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Waist circumferenceconfirming the accumulation of visceral fatin female patientswith depression(> 90cm) has also been reported by otherauthors [5,25]. In the present study, the averagefat content was lowerin female and male urban residents (30% and29%, respectively) compared to female and male village inhabitants (37% and 30%, respectively), although statistically significant difference was found onlybetween women.…”
Section: Discussionsupporting
confidence: 91%
“…Other authors reported lower average VAT (94.6 cm 2 ) and a higher proportion of SAT (389.5 cm 2 ) in comparison with those found in the present study [5]. In patients with depression, waist circumference was strongly correlated with both subcutaneous, r = 0.83 and visceral adipose tissue, r = 0.77, p <0,001) [5].…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations